Antimicrobial Resistance Patterns of Salmonella from Retail Chicken - Berrang, M.E.; Ladely, S.R.; Simmons, M.; Fletcher, D.L.; Fedorka-Cray, P.J. (International Journal of Poultry Science, 2006)
Salmonella is frequently reported as a cause of food-borne illness. The emergence of antimicrobial resistant Salmonella associated with meat products has heightened concerns regarding antimicrobial use in food animal production. Eighty Salmonella isolates recovered from fresh whole chicken carcasses purchased at retail outlets were examined for susceptibility to 18 antimicrobials. Fifteen serotypes were identified; the top five included; S. Heidelberg (25%), S. Typhimurium 5- (formerly var. Copenhagen) (18.75%), S. Kentucky (17.5%), S. Berta (11.25%), and S. Hadar (8.75%). Overall, resistance was most commonly observed to tetracycline (25%), ampicillin (22.5%), streptomycin (21.25%) and cephalosporin derivatives (cephalothin 18.75%, ceftiofur 16.25%, and cefoxitin 15%). Of all isolates, 43.75% were resistant to one or more antimicrobial and 36 % were identified as multi-drug resistant (MDR, resistant to 2 or more antimicrobials). Fourteen resistance patterns were observed and among isolates showing resistance, 22.5% were resistant to 1-3 antimicrobials, 16.25% were resistant to 4-6 antimicrobials, and 5.0% were resistant to = 7 antimicrobials. The prevalence of antimicrobial resistance varied by serotype. All 7 S. Hadar isolates were resistant to 1-2 antimicrobials, 4 of 20 S. Heidelberg isolates were resistant to 1-3 antimicrobials, 10 of 15 S. Typhimurium 5- isolates were resistant to 4-5 antimicrobials, 7 of 14 S. Kentucky isolates were resistant to 1-7 antimicrobials, and 3 of 9 S. Berta isolates expressed resistance to 9-11 antimicrobials. These data indicate that Salmonella recovered from retail poultry carcasses may be resistant to multiple antimicrobials, and that resistance among these isolates varies by serotype.